SOAL HIGHER ORDER THINKING SKILLS (HOTS) MATEMATIKA PADA BUKU TEMATIK TERPADU KURIKULUM 2013 - Norma Dewi Shalikhah; Arif Wiyat Purnanto; Irham Nugroho (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Low ability of students solving the problems can be overcome by accustomed to work on Higher Order Thinking Skills (HOTS) which include analyzing (C4), evaluating (C5) and creating (C6). This study aims to find the distribution of Mathematics questions based on HOTS in integrated thematic textbooks in the 2013 curriculum. Its importance is to give an overview to the government, especially teachers about the quality of these books which are used by schools until 2021. This research is a content analysis with a qualitative approach. Data sources in this study are integrated thematic textbooks of Curriculum 2013 revised edition 2018 for grades I to III SD / MI. The data analysis technique uses percentage analysis. The results showed that the cognitive level of HOTS class I in C4 at 22%, C5 at 4%, C6 at 11%. Class II, C4 at 28%, C5 at 1%, C6 at 6%. Meanwhile, class III, C4 at 29%, C5 at 3%, C6 at 6%. In conclusion, HOTS mathematics questions on cognitive level C4, C5, and C6 in the thematic books of the 2013 curriculum for classes I, II, and III have not reached the criteria for good questions because the percentage of good questions for each cognitive level is C4 40%, C5 30% , and C6 by 30%.